Phenotypic and genotypic susceptibility testing of Mycobacterium tuberculosis cultures from Tshwane Metropolitan area - Lekalakala, M. Ruth (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2015.